2021
DOI: 10.1038/s41598-021-91156-9
|View full text |Cite
|
Sign up to set email alerts
|

Contacts and behaviours of university students during the COVID-19 pandemic at the start of the 2020/2021 academic year

Abstract: University students have unique living, learning and social arrangements which may have implications for infectious disease transmission. To address this data gap, we created CONQUEST (COroNavirus QUESTionnaire), a longitudinal online survey of contacts, behaviour, and COVID-19 symptoms for University of Bristol (UoB) staff/students. Here, we analyse results from 740 students providing 1261 unique records from the start of the 2020/2021 academic year (14/09/2020–01/11/2020), where COVID-19 outbreaks led to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
0
25
1
1
Order By: Relevance
“…In addition, a survey of University of Bristol students found that 99% of students self-isolated after testing positive for COVID-19 and the majority of survey participants reported low contact numbers [38]. However, there was heterogeneity in adherence, with some students reporting many contacts and with only 61% of students with cardinal COVID-19 symptoms self-isolating [38]. In future, it will be important that students maintain their high levels of adherence and to ensure they have sufficient resources to allow them to do so.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a survey of University of Bristol students found that 99% of students self-isolated after testing positive for COVID-19 and the majority of survey participants reported low contact numbers [38]. However, there was heterogeneity in adherence, with some students reporting many contacts and with only 61% of students with cardinal COVID-19 symptoms self-isolating [38]. In future, it will be important that students maintain their high levels of adherence and to ensure they have sufficient resources to allow them to do so.…”
Section: Discussionmentioning
confidence: 99%
“…As 92% of the student population is under 30 years of age, we expect a high proportion of cases to be asymptomatic 19,20 ðf ¼ 0:75Þ. In a survey of university students, a large range of symptoms were reported in participants who tested positive for COVID-19, suggesting that young adults may have symptoms, but not typical ones 21 . We also expect a low hospitalisation rate 22 (h ¼ 0:002) and a low mortality rate of hospitalised cases (μ ¼ 0:038) 22 and have therefore not modelled hospitalisation and death here.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, after such an unclear beginning, other elements were configuring improved versions for the courses depending on the area, emphasis, contents, and semesters where they were allocated. In addition, evaluation was a permanent concern, as well to avoid frauds as to be a purposeful instrument extending the learning during such activity, despite the compromised learning due to the continuous and permanent online sessions, particularly in areas requiring experimentation and practice [65].…”
Section: Didactic Designs Dimensions Improved: Superseding the Traditional Teacher' Knowledge And Perceptionsmentioning
confidence: 99%